ARE WE READY TO INDICATE MYELODYSPLASTIC SYNDROME PATIENTS TO HEMATOPOIETIC STEM CELL TRANSPLANTATION BASED ON THEIR GENETIC STATUS? - de Souza, Mair Pedro; Franceschi, Fernanda Leite Souza; Duarte, Fernando Barroso; Coutinho, Diego; Duarte, Beatrice Araujo; Lemes, Romelia Pinheiro Gonçalves; Colturato, Vergilio (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2020)
Mielodysplastic syndrome and hematopoietic stem cell transplantation based on genetic status.